El ritual - Hayder, Mo (Nuevos tiempos (Madrid, Spain), 2016)
Police diver Flea Marley's discovery of a human hand underwater, as well as evidence that it had been recently amputated while the victim was alive, sends Flea and Detective Inspector Jack Caffery on a search for a young man who recently vanished.